Flexible and Efficient QoS Provisioning in AXI4-Based Network-on-Chip Architecture - Wang, Boqian; Lu, Zhonghai (IEEE transactions on computer-aided design of integrated circuits and systems, 2022)
We propose a network-on-chip (NoC)-based whole system design, whose communication architecture is compatible with the advanced microcontroller bus architecture advanced extensible interface 4 (AXI4) protocol and supports high-performance multiple quality-of-service (QoS) schemes. In our system, the network interface (NI) between the NoC and the master/slave node is proposed to make the NoC architecture independent from the AXI4 protocol via message format conversion between the AXI4 signal format and the packet format, offering high flexibility to the NoC design. Besides, a QoS inheritance mechanism is applied in the slave-side NI to support QoS during packets' round-trip transfer in the NoC. The NoC system contains time-division multiplexing (TDM) and virtual channel (VC) subnetworks to apply multiple QoS schemes to AXI4 signals with different QoS tags, and the NI is responsible for signals distribution between two subnetworks. Besides, a traffic converter is proposed in each NI to balance the traffic between the two subnetworks when necessary. The experimental results show that our proposed architecture ensures a high-throughput and low-latency NoC system. By applying the traffic converter, the packet latency can be improved.